Hemodynamic Effects of Epoprostenol in Patients With Systemic Sclerosis and Pulmonary Hypertension - Strange, Charlie; Bolster, Marcy; Mazur, Joe; Taylor, Marian; Gossage, James R.; Silver, Richard (Chest, 2000)
To determine the cause of pulmonaryhypertension (PH) in systemic sclerosis (SSc) patients since PH canoccur because of pulmonary arteriopathy, pulmonary parenchymaldestruction, and left ventricular cardiac dysfunction. Consecutive case series in a universityhospital. Nine SSc patients with PH (meanpulmonary artery pressure, 41 mm Hg), with (n = 6) or without(n = 3) concomitant interstitial lung disease (ILD). Acute infusion of epoprostenol was begun at 2ng/kg/min and was titrated upward at a rate of 2 ng/kg/min every 30 minuntil symptomatic complications developed or pulmonary artery vascularresistance (PVR) was reduced by 50%. Eightof nine patients demonstrated a reduction of ≥ 20% in PVR, suggesting that vasoreactivity is common despite the presence of significant ILD. A single patient had no response to infusion withunchanged hemodynamics and oxygenation. One patient developed hypoxemiaas cardiac output increased, suggesting a worsening of ventilation/perfusion matching or the presence of an anatomicshunt. Acute pulmonary edema developed in one patient at aninfusion rate of 6 ng/kg/min. The results of cardiac catheterizationsuggested that pulmonary edema was caused by SSc heart disease. SSc patients with ILD have diverse andsometimes multiple causes of PH that can be determined by short-termepoprostenol infusion. Beneficial effects can be obtained fromepoprostenol despite extensive ILD.